Assessment of Risk Factors, Feasibility and Acceptability of VIA for Cervical Cancer Screening and Prevention - Rijal, Pappu; Pradhan, Tarun; Agrawal, A; Rai, R; Bhatta, R; Chhetri, S (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims – To assess feasibility of visual inspection with acetic acid and treatment with cryotherapy for cervical cancer screening and prevention and assess risk factors for cervical cancer in the screened population. Methods – A prospective analysis of all patients enrolled for cervical cancer screening by visual inspection, meeting the eligibility criteria for screening and treatment as per national guidelines 2011 was analyzed form March 2012 to April 2013. Results – A total of 4138 met the eligibility criteria and were counseled for screening, 33 rejected for screening. Out of 4105 screened 241 were visual inspection with acetic acid positive, 211 were treated with cryotherapy, 25 treated with LEEP, 5 rejected to treatment. Mean age of patient in year’s ± SD 41.48 ± 9.72. The visual inspection with acetic acidpositivity rate was 5.9 % Conclusion – Single visit approach is a feasible and acceptable form of cervical cancer screening strategy in our population.